1995
DOI: 10.1177/107319119500200205
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients With HIV-Associated Minor Cognitive/Motor Disorder Exhibit a “Subcortical” Memory Profile? Evidence Using the California Verbal Learning Test

Abstract: A new diagnostic category for HIV seropositive patients–Minor Cognitive/Motor Disorder (MCMD)—was recently proposed by an AIDS task force sponsored by the American Academy of Neurology. Based on past memory research with HIV+ patients who were diagnosed according to the Center for Disease Control (CDC) definition of AIDS, we predicted that HIV+ patients who met the new criteria for MCMD would exhibit a “subcortical” memory profile (i.e., they would display primarily a retrieval deficit). This hypothesis was ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
54
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 34 publications
8
54
1
Order By: Relevance
“…Partial support for this hypothesis was found, as both HIV+ groups demonstrated poorer learning and recall on the CVLT than controls; the two HIV+ antiretroviral-adherence groups did not differ with respect to learning and recall performances. This finding is consistent with data showing verbal learning and recall deficits in HIV+ participants, 2–5,27–29 although it is somewhat inconsistent with data suggesting that HIV-associated neurocognitive deficits might lessen with the use of HAART. 1214 …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Partial support for this hypothesis was found, as both HIV+ groups demonstrated poorer learning and recall on the CVLT than controls; the two HIV+ antiretroviral-adherence groups did not differ with respect to learning and recall performances. This finding is consistent with data showing verbal learning and recall deficits in HIV+ participants, 2–5,27–29 although it is somewhat inconsistent with data suggesting that HIV-associated neurocognitive deficits might lessen with the use of HAART. 1214 …”
Section: Discussionsupporting
confidence: 87%
“…On this basis, some might conjecture that differences in the literature regarding the characterization of HIV-related memory impairment may have been due to disparities in treatment regimens between studies. Specifically, many pre-HAART studies demonstrated both retrieval and encoding deficits 27–29 in HIV+ participants, whereas post-HAART studies indicated that HIV+ participants primarily suffered from an encoding deficit. 2426 However, it is equally possible that the profile of HIV-related memory deficits is somewhat heterogeneous and that those with more pronounced retrieval deficits have greater difficulties with medication adherence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CVLT is regarded as a useful tool for characterizing memory profiles associated with different neuropsychological disturbances, including Alzheimer's disease (AD), Huntington's disease (HD), and Korsakoff 's syndrome (e.g., Delis et al, 1991), HIV-1 infection (Becker et al, 1995;Delis et al, 1995;Peavy et al, 1994;White et al, 1997), depression (Massman et al, 1992), and schizophrenia (Paulsen et al, 1995). The scoring system of the CVLT allows quantification of several indices including style of learning (e.g., semantic categorization of related words), consistency of item recall across learning trials, retention of information over short and longer delays, vulnerability to interference, recall errors (e.g., intrusions), and discriminability (ability to detect target words from distracters on recognition testing).…”
Section: Introductionmentioning
confidence: 99%